Practices of Capital Budgeting Techniques in Manufacturing Enterprises in Kathmandu - Subedi, Santosh (JMC Research Journal, 2020)
The research has been carried out on capital budgeting practices in Manufacturing Enterprises, Kathmandu district with the aim to analyze and evaluate the capital budgeting practices applied by manufacturing firms in Kathmandu district. To accomplish the objective, descriptive research is the process of accumulating facts. The research is to be based on the information of the sample companies through structured questionnaires. For the data analysis and interpretation, percentage was used according to the nature of the data. The application of CB techniques is useful only for large types of organization. Small types of organizations do not want to evaluate project by using CB techniques. Most manufacturing enterprises get advantages after implementation of the CB evaluation techniques. Organizational objectives can be achieved through effective management and use of CB techniques. Most of the sample companies in Kathmandu district are not foregone profitable investment opportunities in view of some limit imposed on the size of capital budget.